PROFITABILITY OF PENSION FUND 1994-2013 - Romero Cerna, José Salvador (2014)
After the reform of the Private Pension System (PPS) and the repeal of obligatory contribution by inde-pendent workers to SPP, the debate on the pension system has focused on a comprehensive reform of it. One of the points at issue is the level of profitability which has filed the pension funds administered by the Pension Fund Administrators (AFP) since its incep-tion (1993), some analysts use the nominal returns (excluding commissions charged by AFP) published by the Superintendency of Banking and Insurance (SBS), and others use the corrected nominal returns (by including commissions).The article estimates the average annual net commis-sions nominal return over a period of 20 years (1994-2013) to determine whether the return on pension funds has been higher than other savings options in the financial system, and based on that formulate public policies.